Research on stability and sensitivity of the rotating machines with overhung rotors to lateral vibrations - Tomasz Szolc; Robert Konowrocki (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2021)
The rotating machines with overhung rotors form a broad class of devices used in many types of industry. For this kind of rotor machine in the paper, there is investigated an influence of dynamic and static unbalance of a rotor, parallel and angular misalignments of shafts, and inner anisotropy of rigid couplings on system dynamic responses. The considerations are performed through a hybrid structural model of the machine rotor-shaft system, consisting of continuous beam finite elements and discrete oscillators. Numerical calculations are carried out for parameters characterizing a heavy blower applied in the mining industry. The main goal of the research is to assess the sensitivity of the imperfections mentioned above on excitation severity of rotor-shaft lateral vibrations and motion stability of the machine in question.